Lateral Position for Cesarean Delivery Because of Severe Aortocaval Compression in a Patient With Marfan Syndrome: A Case Report. Issue 5 (1st March 2017) - Coffman, John C.; Legg, Russell L.; Coffman, Catherine F.; Moran, Kenneth R.
Abstract : Prompt recognition and management of hypotension resulting from aortocaval compression syndrome are essential to optimize the maternal and fetal outcomes. Management involves increasing leftward uterine displacement and sometimes full lateral positioning, although lateral position during cesarean delivery is typically considered to be impractical. We report an obstetric patient case of severe aortocaval compression syndrome resulting in hypotension and loss of consciousness that ultimately underwent cesarean delivery under general anesthesia in the lateral position. Performing cesarean delivery in the lateral position is virtually unreported, and this unique strategy prevented further symptoms of aortocaval compression and enabled safe delivery.